Optimization of depository accounting system of stock and obligation market with application of blockchain - D. I. Kozlov (Статистика и экономика)
Purpose of the study. The first goal of the study is a comparative analysis of the models of the accounting system of the stock market operating on the territory of the Russia, in particular, the model of the distributed accounting system and the model of the centralized accounting with the use of the central depository are considered. The second goal is to apply the distributed ledger technology in the development of a new model for the stock market accounting system. The goals are conditioned by the growing interest to the technology and similarity of its internal processes with the system of accounting of digital assets. The needs in optimization of the existing accounting system, bringing the system to the logical centralization are revealed. The application of distributed ledger technology for the purpose of unification of depository accounting systems is proposed. The analysis of efficiency of the given models is carried out and the criteria of efficiency estimation of each model are revealed. Materials and methods. For carrying out the research the works of description of register system genesis of stock market in Russia were applied. Works of Russian and foreign researchers in the field of influence of technology of distributed registers on accounting system and business processes of organizations are studied. The methodology for comparing models was the approach to the development of highly specialized evaluation criteria that meet the needs of the largest number of stock market participants. Results. Evaluation criteria were developed, on the basis of which the comparison of the existing models of the accounting system of stock market and the projected model on the distributed ledger technology was carried out. The needs for optimization of the existing accounting system of Russia, bring the system to the logical centralization of interaction of elements are revealed. Suggestions for the use of distributed ledger technology in order to unite the register systems of obligations have been developed The variety of elements of the accounting system of the Russian stock market was determined a large number of indicators used in comparisons of models, as well as a variety of approaches, both to the construction of the indicators themselves and to the collection of data to ensure their calculation and comparison. Conclusion. According to the results of the research it was determined that the decentralized model of the stock market accounting system on the distributed ledger technology in comparison with the classic model reduces the transaction cost of obligation right accounting operations, optimizes the complexity of the processes of interaction between the elements of the system, such as depositories and registrars, increases the transparency of the stock market, the processes of the transition of assets rights, due to which the liquidity of such assets and the increases investors interest. Decentralized model standardizes the of communication data, which has a positive effect on the indicators of information systems of participants. In comparison with the centralized model, the decentralized model eliminates the central depository transaction commission, eliminates monopolization to choose the direction of stock market depository accounting system development. Finally, the positive influence of the decentralized model on the stock market as a whole was revealed. The resulting form of relations will reduce the main cost indicators of the accounting system elements, such as transaction costs, the cost of support and development of information systems, the number of necessary formats for the application of interaction with counterparties.